2020
DOI: 10.4269/ajtmh.19-0523
|View full text |Cite
|
Sign up to set email alerts
|

Association of Helicobacter pylori Infection with Vitamin D Deficiency in Infants and Toddlers

Abstract: Helicobacter pylori (H. pylori), a gram-negative pathogen, has been shown to colonize multiple organs and cause various forms of extra-gastrointestinal diseases. The association of H. pylori infection with vitamin D status in apparently healthy children remained unclear; therefore, we investigated the relationship between vitamin D and H. pylori infection among apparently healthy infants and toddlers. In this large cross-sectional study, the examination data of children were collected from January 2013 to Sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
0
18
1
Order By: Relevance
“…Most of the studies that clearly define this relationship have been conducted in the adult age group [6,15]. Limited studies have been conducted on the growth and changes in micronutrient contents of HP infection in childhood [16][17][18][19]. Our research found that the HP positive group had higher median height SDS and median weight SDS than that of controls (Table 1).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Most of the studies that clearly define this relationship have been conducted in the adult age group [6,15]. Limited studies have been conducted on the growth and changes in micronutrient contents of HP infection in childhood [16][17][18][19]. Our research found that the HP positive group had higher median height SDS and median weight SDS than that of controls (Table 1).…”
Section: Discussionmentioning
confidence: 65%
“…The data are very variable in studies examining the relationship between HP infection and developmental delay in children. Janjetic et al could not find an association between hp infection and growth retardation, while Gao et al and Süoglu et al[17,19,20] found a significant level of growth retardation in patients with HP infection. Although HP infection was observed to be accompanied by short stature, its mechanism has not been clearly defined.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, many studies did not report this association, the same as in 25,30 .On the other hand, the hypothesis of Helicobacter pylori infection can lead to a rising risk of development of diabetes in an infected individual. In some studies, diabetic patients are more likely to be infected with Helicobacter pylori, which can have an essential role in this area; some research suggests that Helicobacter pylori infection is more suitable for developing diabetes 33 .On the other hand, individuals infected with Helicobacter pylori have been recorded a low level of vitamin D compared with non-infected individuals; the explanation of this is that Helicobacter pylori effect on D vitamin receptor both at the tissue and the cell levels 41 . Surmeli et al 17 proposed the incorporation of D vitamin to the treatment protocol of some infectious diseases lead to improve the treatment course Some researchers consider a low level of vitamin D to become a risk factor for infection with Helicobacter pylori and cause the failure of its treatment and suggested that to add vitamin D as a therapy to help in the eradication of infection because of antimicrobial effect and played a vital role in gastric mucosa homeostasis and host protection against infection with Helicobacter pylori 15,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Riyadh, Saudi Arabia, 23 and Lagos, Nigeria, 24 show a correlation between H pylori infection and short stature. Similarly, a large cross‐sectional study carried out in China on 6,896 apparently healthy patients 6‐36 months old determined that H pylori seropositive children were more likely to be vitamin D deficient and had a lower weight and height 25 . However, these studies do not provide evidence of causation.…”
Section: Clinical Manifestations Of H Pylorimentioning
confidence: 99%